Attitudes towards video communication for New Medicine Service at community pharmacies - A qualitative pilot study - Camilla Lynnerup; Mikkel Nørreslet; Trine Graabæk (Elsevier, 2022)
Background: New Medicine Service (NMS) is a community pharmacy service that can increase adherence among patients with a newly diagnosed chronic disease. NMS must be carried out by a pharmacist, which is a barrier for some pharmacy units with no pharmacist physically present. Video communication might be a way to overcome this barrier. Objective: This study aims to explore both patients' and community pharmacy staff's attitudes of video-based NMS in a community pharmacy setting. Methods: Semi-structured, telephone interviews were conducted with patients who have participated in video-based NMS. Focus groups with pharmacists who have carried out the video-based NMS and with staff that referred patients to the video-based NMS were conducted at community pharmacies. Thematic inductive analysis was used to analyse the interviews and focus groups. Results: In total, 10 patient interviews were conducted, along with one focus group with four pharmacists and one focus group with 10 referring staff. Three main themes emerged during the analysis: (i) Talking to a screen, (ii) content of the NMS, and (iii) tackling the technique. Patients reported that their questions for the pharmacists were the same as if the NMS had been face-to-face. Pharmacists felt that they appeared more professional on video and that non-medical related conversation was reduced compared with ordinary face-to-face NMS. The referring staff either preferred referring to a video-based NMS over an ordinary face-to-face NMS or had no preferences. Conclusions: Both patients and pharmacy staff had a positive attitude towards the video-based NMS, the content of the NMS and the performance of the IT-system. The consulting time was reduced for video-based NMS compared to face-to-face NMS, but that did not affect the medical related content of the NMS, which indicates that video-based NMS is possible without compromising the health related content.